2020
DOI: 10.1016/j.vacuum.2020.109719
|View full text |Cite
|
Sign up to set email alerts
|

Improving the morphological, optical, and photocatalytic properties of octahedral Zn2SnO4 using Garcinia mangostana fruit peel extract

Abstract: Improving the morphological, optical, and photocatalytic properties of octahedral Zn 2 Sn0 4 using Garcinia man13ostana fruit peel extract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…10b. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The electron affinity (w) of ZnO, SnO 2 , and Zn 2 SnO 4 has been found to be 4.20, 4.20, and 4.50 eV, respectively, 10,39,40,57,58 while the work functions (F) of ZnO, SnO 2 , and Zn 2 SnO 4 have been reported to be 4.71, 4.84, and 4.90 eV, respectively. [59][60][61][62][63][64] It shall be noted that the Fermi level inferred from the literature can only be used for qualitative discussion of oxygen vacancies.…”
Section: Proposed Sensing Mechanismmentioning
confidence: 99%
“…10b. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The electron affinity (w) of ZnO, SnO 2 , and Zn 2 SnO 4 has been found to be 4.20, 4.20, and 4.50 eV, respectively, 10,39,40,57,58 while the work functions (F) of ZnO, SnO 2 , and Zn 2 SnO 4 have been reported to be 4.71, 4.84, and 4.90 eV, respectively. [59][60][61][62][63][64] It shall be noted that the Fermi level inferred from the literature can only be used for qualitative discussion of oxygen vacancies.…”
Section: Proposed Sensing Mechanismmentioning
confidence: 99%
“…Modification using Clitoria ternatea flower extract on ZnAl LDH has been reported by Rohmatullaili et al (2024) , where the modified LDH showed changes in specific characteristics. The use of Garcinia mangostana (GM) pericarp extract has also been reported in the synthesis of gold nanoparticles (Xin Lee et al, 2016), ZnO nanomaterials (Cong et al, 2023), and modification of Zn 2 SnO 4 materials (Angasa et al, 2020). The use of Garcinia mangostana (GM) pericarp extract in modifying LDH-based materials has never been reported before, as it is the novelty of this research.…”
Section: Introductionmentioning
confidence: 85%
“…Importance of research extends to society when metal oxides nanomaterials are derived from waste (industrial, agricultural, food), foreground the concept of “waste towards wealth”. Literature reported the synthesis of ZnO, ZnSn 2 O 4 , CuO, FeO and SnO 2 nanomaterials derived from plant peels [28–32] . In view of environmental concern, green synthesis using phytochemicals (as capping, stabilizing and reducing agents) gained popularity for hybrid nanomaterials [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Literature reported the synthesis of ZnO, ZnSn 2 O 4 , CuO, FeO and SnO 2 nanomaterials derived from plant peels. [28][29][30][31][32] In view of environmental concern, green synthesis using phytochemicals (as capping, stabilizing and reducing agents) gained popularity for hybrid nanomaterials. [33] The plants extract of Eucalyptus spp., A. indica, S. mukkorosi and many more have been used for the synthesis of several metal oxides and Prussian blue analogue.…”
Section: Introductionmentioning
confidence: 99%